Nanomolar Affinity Small Molecule Correctors of Defective ΔF508-CFTR Chloride Channel Gating - Yang, Hong; Shelat, Anang A.; Guy, R.Kiplin; Gopinath, Vadiraj S.; Ma, Tonghui; Du, Kai; Lukacs, Gergely L.; Taddei, Alessandro; Folli, Chiara; Pedemonte, Nicoletta; Galietta, Luis J.V.; Verkman, A.S. (The Journal of biological chemistry, 2003)
Deletion of Phe-508 (ΔF508) is the most common mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) causing cystic fibrosis. ΔF508-CFTR has defects in both channel gating and endoplasmic reticulum-to-plasma membrane processing. We identified six novel classes of high affinity potentiators of defective ΔF508-CFTR Cl– channel gating by screening 100,000 diverse small molecules. Compounds were added 15 min prior to assay of iodide uptake in epithelial cells co-expressing ΔF508-CFTR and a high sensitivity halide indicator (YFP-H148Q/I152L) in which ΔF508-CFTR was targeted to the plasma membrane by culture at 27 °C for 24 h. Thirty-two compounds with submicromolar activating potency were identified; most had tetrahydrobenzothiophene, benzofuran, pyramidinetrione, dihydropyridine, and anthraquinone core structures (360–480 daltons). Further screening of >1000 structural analogs revealed tetrahydrobenzothiophenes that activated ΔF508-CFTR Cl– conductance reversibly with Kd < 100 nm. Single-cell voltage clamp analysis showed characteristic CFTR currents after ΔF508-CFTR activation. Activation required low concentrations of a cAMP agonist, thus mimicking the normal physiological response. A Bayesian computational model was developed using tetrahydrobenzothiophene structure-activity data, yielding insight into the physical character and structural features of active and inactive potentiators and successfully predicting the activity of structural analogs. Efficient potentiation of defective ΔF508-CFTR gating was also demonstrated in human bronchial epithelial cells from a ΔF508 cystic fibrosis subject after 27 °C temperature rescue. In conjunction with correctors of defective ΔF508-CFTR processing, small molecule potentiators of defective ΔF508-CFTR gating may be useful for therapy of cystic fibrosis caused by the ΔF508 mutation.